The Relationship Between Self-Awareness and Blood Pressure Control Compliance in Hypertensive Patients - Riska Febria Putri Lishbet; Hardono (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: The level of compliance among hypertensive patients in Indonesia to undergo routine treatment and blood pressure control is still low. Compliance with blood pressure control in hypertensive patients remains a problem faced until now. Self-awareness in hypertensive patients is one of the factors causing low compliance with routine blood pressure control. This study aimed to determine the relationship between self-awareness and compliance with blood pressure control in hypertensive patients at Batu Ketulis Public Health Center, West Lampung. Method: This research used a quantitative method with an observational analytic design and a cross-sectional approach. The sampling technique used purposive sampling with a total sample of 76 hypertensive patients at Batu Ketulis Public Health Center. The measuring instruments used were medical record data and the self-awareness of hypertension questionnaire. Bivariate analysis used the Chi-Square test. Result: The results showed that most respondents had self-awareness, namely 41 people (53.9%), and most respondents were compliant, namely 39 people (51.3%). The Chi-Square test results obtained 0.000 < 0.05 with an odds ratio (OR) value of 51.81. Conclusion: The conclusion is that patients with a good level of self-awareness have a 51.81 times greater chance (odds) of complying with blood pressure control compared to patients with low self-awareness. It is expected that Batu Ketulis Public Health Center can develop an innovative reminder program for control schedules through a WhatsApp gateway to improve self-awareness and compliance among hypertensive patients.